PAI TEACHER COMPETENCE IMPROVEMENT IN THE PERSPECTIVE OF MADRASAH-BASED MANAGEMENT - Fadlil, Nanang; Agus, Abu Hasan; Mudarris, Badrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In order to realize the achievement of ideal and professional Islamic Religious Education teachers, a managerial approach is needed to increase the competence of these teachers, which includes aspects of planning, organizing, and supervising. The Madrasah-based management approach is very appropriate to use as an analytical knife in order to increase the competence of Islamic Religious Education teachers. This study uses qualitative research with a descriptive approach. This study aims to analyze and understand increasing PAI teachers' competence from the madrasah-based management perspective.